Evolutionary History of RNA Modifications at N6-Adenosine Originating from the R-M System in Eukaryotes and Prokaryotes - Congshan Liu; Jianping Cao; Haobing Zhang; Jianhai Yin (Biology, 2022)
Methylation at the N6-position of adenosine (N6mA) on mRNA (m6A) is one of the most widespread, highly selective and dynamically regulated RNA modifications and plays an important role in transcription and translation. In the present study, a comprehensive analysis of phylogenetic relationships, conserved domain sequence characteristics and protein structure comparisons were employed to explore the distribution of RNA N6mA modification (m6A, m6,6A, m6Am, m6, 6Am and m6t6A)-associated proteins (writers, readers and erasers) in three kingdoms of life and reveal the evolutionary history of these modifications. These findings further confirmed that the restriction-modification (R-M) system is the origin of DNA and RNA N6mA modifications. Among them, the existing mRNA m6A modification system derived from the last eukaryotic common ancestor (LECA) is the evolutionary product of elements from the last universal common ancestor (LUCA) or driven by horizontal gene transfer (HGT) from bacterial elements. The subsequent massive gene gains and losses contribute to the development of unique and diverse functions in distinct species. Particularly, RNA methyltransferases (MTases) as the writer responsible for adding N6mA marks on mRNA and ncRNAs may have evolved from class α and β prokaryotic “orphan” MTases originating from the R-M system. The reader, YTH proteins that specifically recognize the m6A deposit, may be acquired by LECA from an individual prokaryotic YTH-domain protein that evolved from N-terminals of an R-M system endonuclease. The eraser, which emerged from the ALKB family (ALKBH5 and FTO) in eukaryotes, may be driven by independent HTG from bacterial ALKB proteins. The evolutionary history of RNA N6mA modifications was inferred in the present study, which will deepen our understanding of these modifications in different species.